Efek lingkungan kerja terhadap kinerja pegawai kalurahan di Kapanewon Wates, Kulon Progo - Burhanudin, Burhanudin; Anggoro, Tri (Journal of Management and Digital Business, 2026)
This study examines the effect of the work environment on the performance of village employees in Kapanewon Wates, Kulon Progo Regency, Special Region of Yogyakarta. Using a quantitative survey design, the study involved a population of 112 employees and a sample of 60 respondents. Primary data were collected through questionnaires and analyzed using simple linear regression. The findings show that the work environment has a positive and significant effect on employee performance. This result indicates that a more supportive and comfortable work environment is associated with higher employee performance in carrying out public service duties at the village administrative level. The study suggests that kalurahan leaders should enhance workplace quality to improve employee performance. Practical efforts may include providing ergonomic desks and chairs, ensuring adequate lighting and air circulation, reducing workplace noise, and fostering positive relationships between supervisors, subordinates, and coworkers. Overall, the work environment is an important organizational factor in improving employee performance and the quality of local public services.